The Feasibility of Using Rubberwood Bottom Ash in The Mixture of Interlocking Block - Chumprom, Premmanat; Charoennatkul, Charoon; Boonrasi, Pornarai; Laksanakit, Chuthamat; Swasdi, Sommart; Sookmanee, Pongsak; Thongkun, Taweesak (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
The objective of this research is to evaluate the feasibility of using rubberwood bottom ash in the mixture of interlocking blocks. The mixtures were conducted including cement-to-aggregate ratios of 1:4, 1:5, and 1:6 by weight. The rubberwood bottom ash was used as the aggregate as same as laterite soil with different percentages of 0, 10, 30, and 50 by weight of aggregates. The mixtures were compacted using a manual interlocking molding machine. When comparing the research data with the community product standard 602/2547, which specifies that the ompressive strength of non-load-bearing blocks must be no fewer than 25 kg/cm2, and load-bearing blocks should have a compressive strength of no fewer than 70 kg/cm2, and the water absorption should not exceed 288 kg/m3, it is found that all mixtures met the stand for no-load-bearing blocks. While there were three mixtures met the standard for load-bearing blocks consisting of a ratio of cement to aggregate of 1:4 with 0, 10, 30, and 50 percent of rubberwood bottom ash, a ratio of cement to aggregate of 1:5 with 0 and 10 percent of rubberwood bottom ash, and a ratio of cement to aggregate of 1:6 with 0 percent of rubberwood bottom ash.